Peningkatan Kosakata Bahasa Jerman Melalui Model Make A Match - Riskah Basri; Misnawaty Usman; Syukur Saud (Universitas Negeri Makassar, 2021)
Abstract. The purpose of this study was to determine the mastery of German vocabulary of class XI students of SMA Islam Athira 1 Makassar through the make a match model. The type of research used is Classroom Action Research which consists of two cycles, namely cycle I and cycle II, and each cycle consists of four stages, namely, planning, implementation, observation, and reflection. The subjects in this study were class XI students of SMA Islam Athira 1 Makassar, totaling 17 people. Data analysis techniques in this study consisted of qualitative and quantitative. Qualitative data was obtained from the results of observations while quantitative data were obtained from the results of multiple choice tests and essays. The results of the German vocabulary mastery test showed that the average score in the first cycle was 56.76 and increased in the second cycle, which was 78.24. The results of this study indicate that the use of the make a match model can increase the German vocabulary of class XI students of SMA Islam Athira 1 Makassar.